Productive and Reproductive Performance of Different Crossbred Cattle at Sylhet Govt. Dairy Farm - Haque, MN; Haque, MR; Parvin, A; Hussain, MM (Progressive Agriculture, 2013)
The study was conducted at Sylhet Govt. dairy farm to evaluate the productive and reproductive performance of Jersey× Frisian (J×F), Jersey × Local (J×L) and Sahiwal × Local (SL×L.) crossbred during the period of April 2007 to August 2009. Data on milk yield and different reproductive traits like lactation length, milk yield, length of dry period, service per conception, gestation length and post-partum heat period were evaluated. Results indicated that milk yield, length of dry period, service per conception and post-partum heat period were significantly affected (P<0.01) by different crossbred. However, lactation length and service per conception were significantly affected (P<0.01) by parity and interaction of breed × parity. The highest lactation length was observed for the genotype Jersey × Friesian (J×F) and the lowest was Jersey × Local (J×L) in the first and second lactation. The highest milk yield was observed for the genotype J×F and the lowest was J×L. The highest length of dry period was observed in SL× L and lowest was J×F. Furthermore maximum services were required for J×F. The highest gestation length was observed for genotype SL×L. The highest post-partum heat period was observed J×F. The overall reproductive performance of different crossbreds were varied. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16466 Progress. Agric. 22(1 & 2): 47 - 54, 2011